Street Children’s Information Literacy: A Case Study at a Foundation in Bandung - Anwar, R K; Rusmana, A (KnE Social Sciences, 2018)
This study aims to gain an overview of abandoned children’s understanding of information needs, sources of information, how to obtain information, how to evaluate the information obtained, and how to utilize the information obtained. By using mixed-methods research, which involves the collection and analysis of quantitative and qualitative data; this study shows that the street children who are living in a Yayasan Bahtera shelter at Bandung have information literacy. This can be seen from their understanding of the whole information which could be obtained well. Keywords: information literacy, information understanding, street children